Sports and physical activity after cementless total hip arthroplasty with a minimum follow-up of 10 years - Innmann, Moritz Maximilian; Weiss, Stefan; Andreas, Franziska; Merle, Christian; Streit, Marcus R. (Scandinavian journal of medicine & science in sports, 2016)
The present retrospective cohort study was conducted to compare sporting activity levels before and a minimum of 10 years after primary cementless total hip arthroplasty (THA). A consecutive series of 86 patients with a mean age at surgery of 52 years (range, 21-60 years) was evaluated 11 years after surgery (range, 10-12 years). Pre- and post-operative sporting activities were assessed at routine follow-up using the University of California, Los Angeles activity score and the Schulthess Clinic sports and activity questionnaire. Post-operative health-related quality of life was measured using the Short-Form 36 (SF-36) questionnaire and compared with age-matched reference populations from the SF-36 database. Eleven years after THA, 89% of preoperatively active patients had returned to sport. Comparing sports activity preoperatively (before the onset of symptoms) and 11 years after THA, no significant difference was found for the mean number of disciplines or session length. A significant decline in high-impact activities was observed, while participation in low-impact activities significantly increased. Health-related quality of life compared well against a healthy age-matched reference population and was significantly higher than in a reference group of patients with osteoarthritis. The majority of patients were able to maintain their physical activity level in the long term after primary cementless THA, compared with the activity level before the onset of restricting osteoarthritis symptoms. However, a change in disciplines toward low-impact activities was observed.
First published: 03 June 2015
Gesehen am 30.04.2020